“É preciso transver o mundo”: a sensibilidade na educação linguística com crianças na perspectiva plural - Malta, Liliane Salera (2024)
This dissertation, entitled "It is necessary to see the world anew: sensitivity in linguistic education with children from a plural perspective," suggests a reflection on the challenges and possibilities of linguistic education with children, proposing a sensitive, plural, and critical approach that breaks with traditional and uniform paradigms. Situated within the context of growing interest in teaching English in early childhood education, the research problematizes the underlying motivations for this expansion, questioning market-driven notions while, as a counterpoint, recognizing the importance of sensitizing children to languages and cultures. The main objective of the research is to conceive linguistic education with children as a plural space, intertwining multiple perspectives — those of children, pre-service teachers, and the author as both educator and researcher. The dissertation also seeks to reflect on the theoretical and practical foundations of teacher education and pedagogical praxis in this scenario, while proposing a critique of the normativity present in curricula and the neoliberal and colonial influences in language teaching. Methodologically, the research adopts an autoethnographic approach, combining personal experience with data collected through classroom observations, interactions with children, questionnaires applied to pre-service teachers, and social media posts. This methodological choice enables the articulation of emotional, social, and professional aspects involved in linguistic education with children while emphasizing the complexity of educational practices and the uniqueness of children's experiences. The reflections are supported by a broad theoretical framework, including concepts from Freirean critical education, rhizomatic thinking, transdisciplinarity, translanguaging, and decoloniality. Critical education, inspired by Paulo Freire, underpins the appreciation of reflective and emancipatory praxis, while rhizomatic thinking challenges linear approaches, proposing disruptions and multiple connections. Transdisciplinarity highlights the need to integrate different forms of knowledge and disciplines into the educational process, while translanguaging contributes to mitigating power hierarchies in the classroom. The decolonial perspective challenges colonial structures in language teaching, advocating for the appreciation of local epistemologies and the overcoming of homogenizing practices. The research findings highlight that linguistic education with children benefits from praxiologies that value plurality and children's protagonism. By including children’s voices as agents of knowledge production, the research breaks with traditional views that treat them merely as passive recipients. The integration of multiple perspectives — those of children, pre-service teachers, and the author as a researcher — reveals the richness of teaching based on shared experiences and critical reflections. The research underscores the need to reformulate teacher education curricula to incorporate praxis that aligns theory and practice in a more integrated and dialogic way. Such an inseparability must be sensitive to cultural and social specificities, especially in contexts marked by inequalities and historically rooted power dynamics. As its main contribution, the dissertation conceives perspectives in linguistic education based on sensitivity, plurality, and a break from colonial and neoliberal paradigms. Finally, it is understood that this approach broadens the role of education as a space for social transformation, encouraging praxiologies that promote autonomy, criticality, and the appreciation of diverse voices in the educational process.